Gender violence: an evolutionary analysis of the concept - Jaramillo-Bolivar, Cruz Deicy; Canaval-Erazo, Gladys Eugenia (Universidad y Salud, 2020)
Introduction: A concept is an idea about something or an action. Objective: To analyze the concept of “Gender Violence” from the Rodgers’ evolutionary perspective. Materials and methods: An evolutionary analysis of this concept was carried out through a review of literature published between 2000 and 2018. The inclusion criteria were: research articles related to implementation of strategies and politics; thesis; books; book chapters; and reports. They were found in the databases of Lilacs, Ebsco, SciELO, CINAHL, Web of Science, PubMed, and Google Scholar. The review also included documents from international organizations published from 2000 to 2018 in Spanish, English or Portuguese, which discussed Ibero-American issues. Results: Gender violence is a phenomenon with structural, social and political dimensions and is caused by the structural discrimination triggered by a sex-gender-patriarchy system. Related terms such as gender inequality, control, asymmetric relationships were found. Likewise, surrogate terms, i.e., violence against intimate partners, women and domestic violence, were also identified. Conclusions: Gender violence constitutes a violation against human rights that affects the dignity, physical and moral integrity, freedom, and autonomy of people.